If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-2x + -2) = 12 Reorder the terms: -3(-2 + -2x) = 12 (-2 * -3 + -2x * -3) = 12 (6 + 6x) = 12 Solving 6 + 6x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = 12 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 12 + -6 6x = 12 + -6 Combine like terms: 12 + -6 = 6 6x = 6 Divide each side by '6'. x = 1 Simplifying x = 1
| 2.6=3a | | 7b-10+69-3=83 | | y-42=180 | | 8(1+5)+5=12+5x | | 1-4lnx=lnx-9 | | 10f+8=11f+7 | | 6(y+1)=2y+18 | | 4m+10=36 | | 23+5x=111-3x | | 7(51)=10 | | -2(3-7)-4= | | x=11+7y | | 2b+b=7 | | 13+3x=3n-29 | | 3y-2=4(2y-3) | | 13+3x=-29-3n | | 2.6=0.2-4 | | -2a+(5a-3)-(3a+4)= | | 8-3k+6k=2k-3 | | -4(x+3)-7=-3x-15 | | 6(w-3)-(2w-5)=3w | | y=-8/9x-8/9 | | -5+7x+7=8(x+3)-9 | | 12R=1/4M-5 | | 4x-28y=44 | | -2y+13=14-y | | g(p+2)=3x^2+3x+1 | | -2-k=-8 | | -4c+18=5c | | (1/3)9squarred | | 7x+8-5x=-2 | | 7b+3=5b-11 |